Novel Epigenetic Biomarkers Mediating Bisphenol A Exposure and Metabolic Phenotypes in Female Mice - Anderson, Olivia S. (Endocrinology, 2016)
There is compelling evidence that epigenetic modifications link developmental environmental insults to adult disease susceptibility. Animal studies have associated perinatal bisphenol A (BPA) exposure to altered DNA methylation, but these studies are often limited to candidate gene and global non–loci-specific approaches. By using an epigenome-wide discovery platform, we elucidated epigenetic alterations in liver tissue from adult mice offspring (10 months) following perinatal BPA exposure at human physiologically relevant doses (50-ng, 50-μg, and 50-mg BPA/kg diet). Biological pathway analysis identified an enrichment of significant differentially methylated regions in metabolic pathways among females. Furthermore, through the use of top enriched biological pathways, 4 candidate genes were chosen to assess DNA methylation as a mediating factor linking the association of perinatal BPA exposure to metabolic phenotypes previously observed in female offspring. DNA methylation status at Janus kinase-2 (Jak-2), retinoid X receptor (Rxr), regulatory factor x-associated protein (Rfxap), and transmembrane protein 238 (Tmem238) was used within a mediational regression analysis. DNA methylation in all four of the candidate genes was identified as a mediator in the mechanistic pathway of developmental BPA exposure and female-specific energy expenditure, body weight, and body fat phenotypes. Data generated from this study are crucial for deciphering the mechanistic role of epigenetics in the pathogenesis of chronic disease and the development of epigenetic-based prevention and therapeutic strategies for complex human disease.